2011
DOI: 10.1007/s00421-011-1908-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical and mental task demands on cervical and upper limb muscle activity and physiological responses during computer tasks and recovery periods

Abstract: The present study examined the effects of physical and mental workload during computer tasks on muscle activity and physiological measures. Activity in cervical postural muscles and distal forearm muscles, heart rate and blood pressure were compared among three tasks and rest periods of 15 min each in an experimental study design. Fourteen healthy pain-free adults participated (7 males, mean age = 23.2 ± 3.0 years) and the tasks were: (1) copy-typing ("typing"), (2) typing at progressively faster speed ("pacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(105 reference statements)
2
24
0
3
Order By: Relevance
“…One group found that when a certain psychosocial stress exists, the trapezius muscle will become affected and the muscle activity will be increased significantly [8,12,18,21,[29][30][31]35]. On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28]. Meanwhile, there are several studies that can be categorized in a third group where this group obtained a combination of the two aforementioned results [1,25,26,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One group found that when a certain psychosocial stress exists, the trapezius muscle will become affected and the muscle activity will be increased significantly [8,12,18,21,[29][30][31]35]. On the other hand, another group of researchers found that the existence of a certain psychosocial stress did not have any significant effect on trapezius muscle activity [9,14,18,19,23,24,27,28]. Meanwhile, there are several studies that can be categorized in a third group where this group obtained a combination of the two aforementioned results [1,25,26,29].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies used plain copying as a baseline for muscle activity [1,14,20,27,28]. The participants need to copy some text at their own comfortable pace and condition.…”
Section: Plain Copyingmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, mental stress levels are known to increase with the duration of computer-related tasks. Mental stress affects autonomic nerve activity [13][14][15][16] in CRDs caused by tasks that are performed under time constraints (for example, to meet deadlines) [17][18][19] or require speedy performance [16]. Although computers are operated using keyboards, touchpads, and mouse devices, CRDs and computer arm syndrome can even be associated with tasks involving IJOMEH 2014;27(4)…”
Section: Introductionmentioning
confidence: 99%